The Life Crafting Scale: Development and Validation of a Multi-Dimensional Meaning-Making Measure - Chen, Shi; van der Meij, Leander; van Zyl, Llewellyn E.; Demerouti, Evangelia (Frontiers in Psychology, 2022)
Finding meaning in our lives is a central tenet to the human experience and a core contributor to mental health. Individuals tend to actively seek the sources of meaning in their lives or consciously enact efforts to create or “craft” meaning in different life domains. These overall “Life Crafting” behaviors refer to the conscious efforts individuals exert to create meaning in their lives through (a) cognitively (re-)framing how they view life, (b) seeking social support systems to manage life challenges, and (c) actively seeking challenges to facilitate personal growth. Specifically, these behaviors are actioned to better align life goals, personal needs, values, and capabilities. However, no psychological assessment instrument currently exists to measure overall life crafting. As such, the purpose of this paper was twofold: to conceptualize life crafting and to develop, validate and evaluate a robust measure of overall life crafting. A mixed-method, multi-study research design was employed. First, nine participants were interviewed to determine the methods or techniques used to craft meaningful life experiences. These methods/techniques were used as indicators to create an initial item pool which was then reviewed by a panel of experts to ensure face validity. Second, in Study 1, the factorial structure of the instrument was explored by gathering data from a convenience sample (N = 331), with the results showing support for a three-factor structure of life crafting, consisting of (a) cognitive crafting, (b) seek social support, and (c) seek challenges. Finally, in Study 2 (N=362), the aim was to confirm the factorial structure of the Life Crafting scale and to determine its level of internal consistency, partial measurement invariance across genders, and criterion validity (meaning in life (β = 0.91), mental health (β = 0.91), work engagement (β = 0.54), and job burnout (β = -0.42)). The results supported a second-order factorial model of Life Crafting, which comprised of three first-order factors (cognitive crafting, seeking social support, and seeking challenges). Therefore, the Life Crafting Scale can be used as a valid and reliable instrument to measure- and track the effectiveness of life crafting interventions.